Maximizing Productive Zakat Earnings through Internal Supervision Strategy in Zakat Organizations - Agusti, Netta; Arsela, Mika; Ashari, Fadli (UIN Fatmawati Sukarno Bengkulu, 2022)
This study discusses the implementation of internal control to maximize the acquisition of productive zakat funds in the Bengkulu Branch of the Indonesian Zakat Initiative. This research uses qualitative based on primary and secondary data. Data collection techniques using observation, interviews, and documentation. To test the validity of the data, researchers used triangulation analysis. The study results found that internal control for Productive Zakat at the Indonesian Zakat Initiative Bengkulu Branch begins with tidying up the data and distributing the data to each member in the related field. Each member gets a regular schedule. Part of this work is done manually and partly using an e-donation application. The best supervisors get awards for achieving work targets and provide sanctions/reprimands for those who do not complete their work targets. Finally, this study recommends further discussing effective zakat control in Indonesian zakat initiatives.